6x + 2y = -3
To put this in the form y = mx + b, try and isolate the y. I'll show you in steps.
First, move the 6x to the right hand side.
2y = -6x - 3
Now, divide both sides by 2. At the same time, what you're going to do is individually put each of the terms on the right hand side over 2.
y = (-6/2)x - (3/2)
Of course, we get a fraction reduction.
y = -3x - (3/2)
And there you have it; y = mx + b form.
2007-03-10 18:20:43
·
answer #1
·
answered by Puggy 7
·
0⤊
1⤋
6x+2y=-3 subtract 6x from each side
2y=-6x-3 divide both sides by 2
y=-3x-3/2
2007-03-11 03:28:35
·
answer #2
·
answered by yupchagee 7
·
0⤊
0⤋
6X+2Y=-3
isolate the 2y by subtracting 6x from both sides
6x-6x+2y=-3-6x
2y = -6x-3
divide both sides by 2
2/2y = -6x/2 -3/2
y = -3x - 3/2
answer
y = -3x -3/2
2007-03-11 03:19:24
·
answer #3
·
answered by Bill F 6
·
1⤊
0⤋
2y = - 3 - 6x
2y = - 6x - 3
y = - 3x - 3 / 2 (m = - 3, b = - 3 / 2)
2007-03-11 03:44:25
·
answer #4
·
answered by Como 7
·
0⤊
0⤋
2y=-3-6x
y =(-3(2x+1))/2
Dexter T
2007-03-11 03:20:06
·
answer #5
·
answered by Anonymous
·
0⤊
0⤋
6x+2y=-3
6x= -3-2y
this is it...since the variables are different you cannot add or subtract them.
2007-03-11 03:21:13
·
answer #6
·
answered by love....me 2
·
0⤊
0⤋
6x+2y= -3
2y = -3 - 6x
y = (-3/2 - 3x)
:==:
2007-03-11 03:46:24
·
answer #7
·
answered by aeiou 7
·
0⤊
0⤋
y=-3x-3/2
or
y=(-3)x + (-3/2)
where
m=-3
b=-3/2
2007-03-11 04:09:22
·
answer #8
·
answered by Ho K 3
·
0⤊
0⤋